Assessment of Thyroid Function in Neonates Born to Hypothyroid Mothers - Ray, Nabal Kishor; Rimal, Hem Sagar; Mishra, Rajnish; Yadav, Shailendra Kumar; Singh, Ishani (Birat Journal of Health Sciences, 2022)
Introduction: Congenital hypothyroidism is a preventable cause of intellectual disability in childhood. It is one of the commonest endocrine conditions encountered in the neonatal period. Maternal Thyroid Status has long been recognized as having an impact on the developing fetus, and more recently a family history of thyroid dysfunction has been implicated as a risk factor in congenital hypothyroidism (CH). Therefore, this study focused on thyroid screening in neonates born to hypothyroid mothers. Objective: The aim of this study was to assess the thyroid function in neonates born to hypothyroid mothers. Methodology: This was a hospital based cross-sectional observational prospective study conducted at Birat Medical College and Teaching Hospital from March 2021 to May 2022. A total of 109 neonates born to hypothyroid mothers were included in the study. Thyroid functions of these babies were assessed at 72 hours of life. The data was entered into Microsoft offices excel and analyzed using statistical package for social sciences (SPSS 20). Results: Out of 109 neonates born to hypothyroid mothers, <1% was found to have a high TSH Level above the upper limit of reference cut off value (20miu/L) and was considered to be abnormal (congenital hypothyroidism). Conclusion: All the newborns except one had normal TSH levels which were probably due to early diagnosis and timely initiation of treatment to the mothers with hypothyroidism.